2015
DOI: 10.1186/s13019-015-0385-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of pericardiectomy for constrictive pericarditis

Abstract: BackgroundConstrictive pericarditis is a rare and disabling disease that can result in chronic fibrous thickening of the pericardium. The purpose of this study was to evaluate the long-term outcomes following treatment of constrictive pericarditis by pericardiectomy.MethodsBetween September 1992 and May 2014, 47 patients who underwent pericardiectomy for constrictive pericarditis were retrospectively examined. Demographic, pre-, intra- and postoperative data and long-term outcomes were analyzed.ResultsThirty o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 10 publications
6
44
0
Order By: Relevance
“…Previous studies have only reported postoperative morbidity and mortality results after pericardiectomy in clinical cases (McCaughan et al, 1985;Hardy et al, 1992;Wood et al, 2002;Schofield et al, 2004;Nath et al, 2014;Bicer et al, 2015;Busch et al, 2015;Vistarini et al, 2015). The question about histopathologic formation of the adjacent surfaces between lung and heart tissues and its effect on heart functions has not been clearly investigated yet.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have only reported postoperative morbidity and mortality results after pericardiectomy in clinical cases (McCaughan et al, 1985;Hardy et al, 1992;Wood et al, 2002;Schofield et al, 2004;Nath et al, 2014;Bicer et al, 2015;Busch et al, 2015;Vistarini et al, 2015). The question about histopathologic formation of the adjacent surfaces between lung and heart tissues and its effect on heart functions has not been clearly investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…disturbance, shock, oliguria and prolonged anesthesia time (Jackson et al, 1999) thoracoscopy is preferred to manage pericardial disease and effusions (Jackson et al, 1999;Palsgaard et al, 2007;Bicer et al, 2015). Considering this and previous postoperative clinical results, comparative investigation of the partial pericardiectomy through thoracotomy and thoracoscopic pericardial window techniques was planned in an experimental animal model.…”
Section: Histopathological Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a smaller cohort of 47 patients (46.8% due to TBP) from Turkey, followed out to 61.2 ± 66 months, the rate of recurrent CP was zero. (53) All but one patient underwent pericardiectomy via median sternotomy with radical pericardial resection. HIV status was not reported on and most patients had a preoperative NYHA class of II or III.…”
Section: Volume 13 Numbermentioning
confidence: 99%